PROSTATE CANCER MANAGEMENT IN MOEWARDI HOSPITAL SURAKARTA FROM JANUARY 2000 – DECEMBER 2006 - Mahadi, Endi Prilansa; Widjanarko, Suharto (Indonesian Urological Association, 2009)
Objective: To describe the prostate cancer management in Dr. Moewardi Hospital Surakarta on January 2000 – December 2006. Materials & Methods: This study is a retrospective descriptive. The data was collected from Dr. Moewardi Hospital Surakarta’s medical record in seven years, from January 2000 to December 2006. Results: We found that thirty patients with prostate cancer with age above 50 years and mostly found on age 71 – 75 years (23,3%). The most common complain that can be found are LUTS (76,7%). Malignancies was found on digital rectal examination on 76,7% patients. About 28 patients with PSA level > 4ng. Most of the patients (20/66,7%) comes with T2 stadium and seven of them (23,3%) with metastize to the pelvic bone. All of the patient was administered with TUR-P, 7 patients with metastize administered to orchidectomy and hormonal therapy (23,3%), and only one of them continued with radiotheraphy. All of the prostate materials that analyze on pathyologic examination are adenocarcinoma of the prostate with 50% speciments are poorly differentiated. Conclusion: From thirty patients diagnozed with prostate cancer, most of them was found between 71 – 75 years old. The common complain are urinary retention, LUTS and pelvic bone metastize. The pathologic examination we shows all of the speciments are adenocarcinoma of the prostate and they are poorly differentiated.